FRI0281 Transcriptomic profiling of pdcs from patients with pss identifies consistently altered gene networks that indicate an activated phenotype and enhanced anti-viral state. (12th June 2018) - Hillen, M.R.; Pandit, A.; Blokland, S.L.M.; Hartgring, S.A.Y.; Van der Wurff-Jacobs, K.M.G.; Kruize, A.A.; Rossato, M.; van Roon, J.A.G.; Radstake, T. R. D.J.
Abstract : Background: Primary Sjögren's syndrome is an autoimmune disease characterised by lymphocytic infiltration of the exocrine glands and dryness of mouth and eyes. Type-I interferons (IFN) are thought to play an important role in pSS pathogenesis and plasmacytoid dendritic cells (pDCs) are capable of producing high levels of IFN. These cells infiltrate the salivary glands of pSS patients and their numbers correlate with local IFN-production. Objectives: To understand the molecular mechanisms behind systemic dysregulation of pDCs, we performed RNA sequencing on pDCs isolated from peripheral blood of patients with pSS, non-Sjögren's sicca (nSS) and healthy controls. Methods: We established two independent cohorts (each n=31), of patients and controls. pSS patients (n=25) were classified according to the 2002 AECG criteria. nSS patients (n=20) presented with dryness complaints without a known cause, did not have any generalised autoimmune disease, and did not fulfil the classification criteria for pSS. Healthy donors (n=17) were included as control group. Peripheral blood pDCs were isolated using MACS and RNA sequencing was performed for both cohorts.±20 million paired-end sequencing reads per sample were obtained using using Illumina HiSeq 2500 platform. Results: 8556 genes were differentially expressed (p-value<0.05) between all three groups in the discovery cohort. Of these, 3144 genes were also differential in the replication cohort. We generated gene modules from both cohorts and found 5 gene clusters comprising 1259 genes that were consistently dysregulated in both analyses. Pathway analysis showed that the 5 modules contain genes associated with cellular activation, including a group of genes involved in IFN-signalling and viral sensing, as well as regulation of intracellular transport. Generally, pDCs from patients with nSS displayed an intermediate phenotype. Conclusions: We mapped transcriptomic differences in circulating pDCs from patients with nSS and pSS and identified gene clusters that are robustly replicated in two independent cohorts. We found 5 gene clusters that are dysregulated in patients with pSS and indicate enhanced cellular activation, including IFN-signalling and viral sensing which are key pathways in pSS pathogenesis. nSS patients showed similar transcriptomic dysregulation at an intermediate level. These data can help us better understand the role of pDCs in pSS. Disclosure of Interest: None declared